2020
DOI: 10.3390/polym12030558
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Encrustation on Ureteral Stents: Which Surface Parameters Provide Guidance for the Development of Novel Stent Materials?

Abstract: Encrustations of ureteral stents are one of the biggest problems with urological implants. Crystalline biofilms can occur alone or in combination with bacterial biofilms. To identify which surface parameters provide guidance for the development of novel stent materials, we used an in vitro encrustation system. Synthetic urine with increasing pH to simulate an infection situation was pumped over the polymer samples with adjusted flow rates at 37 °C to mimic the native body urine flow. Chemical surface features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 26 publications
(40 reference statements)
1
25
0
Order By: Relevance
“…The problems encountered in ureteral stents also instigated companies to develop optimized polyurethane-based proprietary formulations, like Sof-Flex ®, Tecoflex ® , Hydrothane ® and ChronoFlex ® [13]. Nowadays, polyurethane's chemical characteristics can be tuned, such as the surface wettability and surface energy, which allows the control of other properties like encrustation and bacterial adhesion propensity [14]. Other polymers were also developed, such as the polyester copolymer, Silitek ® , a proprietary polymer that becomes soft and flexible at body temperature, with a reported excellent biocompatibility, Perculfex ® , polyethylene-vinyl acetate and styrene/ethylenebutylene/styrene block copolymers, F-Flex ® , and poly(methyl methacrylate)/poly(hydroxyethyl methacrylate) (PMMA/pHEMA) with improved mechanical properties than silicone [15].…”
Section: Polymeric Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The problems encountered in ureteral stents also instigated companies to develop optimized polyurethane-based proprietary formulations, like Sof-Flex ®, Tecoflex ® , Hydrothane ® and ChronoFlex ® [13]. Nowadays, polyurethane's chemical characteristics can be tuned, such as the surface wettability and surface energy, which allows the control of other properties like encrustation and bacterial adhesion propensity [14]. Other polymers were also developed, such as the polyester copolymer, Silitek ® , a proprietary polymer that becomes soft and flexible at body temperature, with a reported excellent biocompatibility, Perculfex ® , polyethylene-vinyl acetate and styrene/ethylenebutylene/styrene block copolymers, F-Flex ® , and poly(methyl methacrylate)/poly(hydroxyethyl methacrylate) (PMMA/pHEMA) with improved mechanical properties than silicone [15].…”
Section: Polymeric Materialsmentioning
confidence: 99%
“…Albeit all the reported polymer's formulations, the available ureteral stents are not devoid of clinical complications, thereby, investigations aiming to modify the base polymers are still on going. A recent work presented by Rebl et al addressed the influence of physical properties of different polymers' samples on their propensity to develop encrustation [14]. The data revealed that the encrustation degree is correlated with the surface charge and hydrophobicity of the polymer samples, a lower encrustation propensity was observed for polymers with strong negative surface charge and good hydrophilicity [14].…”
Section: Polymeric Materialsmentioning
confidence: 99%
“…Heparin, having a strong negative charge density is a potent inhibitor of encrustations and is often incorporated as a coating material in commercially available ureteral stents. However, its effectiveness to prevent biofilm is still a matter of debate [72,73]. In contrast, the contact-killing strategy relies on a positively charged surface and a permeabilization of the bacterial cell surface that leads to the leakage of intracellular material and eventual cell death.…”
Section: Electrical Charges To Prevent Biofilm Adhesionmentioning
confidence: 99%
“…It was revealed that a change in the calcium and magnesium salts ratio and albumin concentration altered the mass of encrustation. Moreover, the surface properties with good hydrophilicity, stable zeta potential and the presence of urease inhibitors significantly produced promising ureteral stents [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%